INTEGRATING DIGITAL TECHNOLOGIES INTO GENERATION Z MARKETING STRATEGIES: STUDYING VALUES, CHANNEL EFFECTIVENESS, AND CONSUMER TRENDS - Kovalchuk, Svitlana; Tsurska, Bohdana; Bondarchuk, Katerina Bondarchuk; Uzhva, Roman; Shevchuk, Roman (Revista Gestão & Tecnologia, 2024)
Objective – The purpose of this study is to identify Gen Z values and related communication channels and consumer trends when integrating digital technologies into marketing campaigns. Methodology – The systematic literature review was the main methodology of the literature, during which it was possible to identify 12 studies in the databases Scopus and Google Scholar that could help achieve the objective of the study. Originality/relevance – This study helped identify the most effective marketing strategies for Generation Z and the related characteristics of advertising activities. Results – As a result of the analysis, it became clear that the most appropriate communication channel was social networks, based on the consumer preferences and values of the target consumer group, combined with neuromarketing. Contribution – The results may be useful to marketers as they conduct digital advertising activities targeting members of Generation Z.